Evaluation of in vitro aldose reductase inhibitory potential of different fraction of Hybanthus enneaspermus Linn F. Muell - Patel D.K.; Kumar R.; Kumar M.; Sairam K.; Hemalatha S. (My University, 2025)
Objective: To evaluate the aldose reductase inhibitory (ARI) activity of different fractions of Hybanthus enneaspermus for potential use in diabetic cataract. Methods: Total phenol and flavonoid content of different fractions was determined. ARI activity of different fractions in rat lens was investigated in vitro. Results: The results showed significant level of phenolic and flavonoid content in ethyl acetate fraction [total phenol (212.15±0.79 mg/g), total flavonoid (39.11 ± 2.27 mg/g)] and aqueous fraction [total phenol (140.62±0.57 mg/g), total flavonoid (26.07±1.49 mg/g)] as compared with the chloroform fraction [total phenol (68.56±0.51 mg/g), total flavonoid (13.41 ± 0.82 mg/g)] and petrolium ether fraction [total phenol (36.68±0.43 mg/g), total flavonoid (11.55±1.06 mg/g)]. There was a significant difference in the ARI activity of each fraction, and it was found to be the highest in ethyl acetate fraction [IC50 (49.26±1.76 μ g/mL)] followed by aqueous extract [IC50 (70.83±2.82 μg/mL)] and it was least in the petroleum ether fraction [IC50 (118.89±0.71 μg/mL)]. Chloroform fraction showed moderate activity [IC50 (98.52±1.80 μ g/mL)]. Conclusions: Different fractions showed significanct amount of ARI activity, where in ethyl acetate fraction it was found to be maximum which may be due to its high phenolic and flavonoid content. The extract after further evaluation may be used in the treatment of diabetic cataract.